Kesiapan Menghadapi Menarche pada Remaja Putri Prapubertas Ditinjau dari Kelekatan Aman Anak dan Ibu - Nurul Hidayah; Sara Palila (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2018)
This study aims to determine the relationship between mother’s secure attachment to the readiness of prepubertal girl to face first menstruation (menarche). The participants were 74 elementary students at V and VI grade in Budi Mulia Elementary School, Seturan. This study used quantitative research method. Measuring instruments were menarche preparedness scale and secure attachment scale. Hypothesis testing was conducted using a statistical technique test of Pearson Product Moment Correlation with SPSS software. The results showed a correlation coefficient (rxy) = .305 with significance level of p=.008 (p<.01), so the hypothesis was accepted. This result indicates that there is a significant positive correlation between mother’s secure attachment to the pre-pubertal girls’ readiness to face first menstruation (menarche).